Analyzing Collaborative Interaction In Learners’ Task-Based Oral Discourse - Zakaria, Abd Razak (Advances in Social Sciences Research Journal, 2014)
<!–[if gte mso 9]> <![endif]–> The aim of the study was to investigate how learners of English as a foreign language (EFL) interacted during task completion using two different communication task types i.e. jigsaw and decision-making. The focus of investigations was the dynamics of learner interaction and the kind of oral discourse generated by the participants. The data for the study comprised transcribed recordings of learner interactions working on given tasks. They were qualitatively analyzed focusing on the social processing. Findings revealed that the participants attempted task completion collaboratively. The collaborative interaction was characterized by argumentative episodes. However, close examination showed that the participants engaged in more intensive argumentative negotiations which were highly collaborative during decision-making task completion than during task completion of the jigsaw task type. The results suggest that communication task types elicited collaborative interaction episodes with argumentative negotiations and these kinds of interactions are believed to be important particularly for learners at the tertiary level. <p class="MsoListParagraph" style="margin-top: 0cm; margin-right: 0cm; margin-bottom: 10.0pt; margin-left: 0cm; mso-add-space: auto; text-align: justify; mso-pagination: widow-orphan; mso-layout-grid-align: auto; punctuation-wrap: hanging;">Keywords: oral discourse, collaborative interaction, argumentative episodes, communication tasks <!–[if gte mso 9]> Normal 0 21 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>